Inquiries on dynamics of transition economy convergence in a two-country model - Jan Bruha; Jirí Podpiera (European Central Bank (ECB), 2007)
In this paper we propose an extension to New International Macroeconomic framework by introducing the vertical investment margin. The dynamic properties of the extended model are discussed in relation to relevant existing models with particular emphasis on the impact of productivity convergence and effects of timing of trade and financial liberalization on the convergence patterns. We compare the mechanisms behind the three investment margins (horizontal investment to new varieties, vertical investment to quality, and investment to export-eligibility) for the long-run equilibrium. Based on such comparison, the proposed extension proves crucial for consistent explanation of long-term trends in macroeconomic aggregates and the real exchange rate development observed in European transition countries.
Keywords: F12; F36; F41; 330; convergence; New International Macroeconomics; Two-country modeling; Wirtschaftliche Konvergenz; Schwellenländer; Zwei-Länder-Modell; Neue Makroökonomik offener Volkswirtschaften